Recovery from daily-life stressors in early and chronic psychosis - Vaessen, Thomas; Reininghaus, Ulrich (Schizophrenia research, 2019)
Initial affective and psychotic reactivity to daily stressors is altered in psychosis, and most notably in early psychosis. In addition to altered initial stress reactivity, results from studies using Experience Sampling Methodology (ESM) and psychophysiological measures indicate that impaired recovery from mild stressors may also be a risk factor for mental illness. The current ESM study investigated affective recovery from daily stressors in chronic psychosis patients (CP; n=162), individuals at early stages of psychosis (EP; n=127), and healthy volunteers (HV; n=220) assessing fluctuations in negative affect (NA), tension, and suspiciousness ten times a day on six consecutive days. Recovery was operationalized for all three variables as the return to baseline (i.e., level at t−1) following the first stressful event of a day (i.e., t0). The EP group showed a delayed recovery of NA (t1-t3: B=0.185; p=.007 and B=0.228; p=.002) and suspiciousness (t1: B=0.223; p=.010 and B=0.291; p=.002) compared to HV and CP, respectively. Delayed recovery was detected for tension as well (t1-t2: EP>HV: B=0.242; p=.040 and EP>CP: B=0.284; p=.023), but contrary to both other momentary states, this effect disappeared when controlling for subsequent stressful events. There were no significant differences in recovery between HV and CP. These results suggest that in EP, stressful daily events have longer-lasting effects on overall negative affect and subclinical psychotic-like experiences. Future studies should incorporate physiological and endocrine measures in order to integrate recovery patterns of the different stress systems.